Workforce Reduction, Subjective Job Insecurity, and Mental Health - Reichert, Arndt R.; Tauchmann, Harald (Elsevier, 2017)
We examine the link between workforce reduction, subjective job insecurity, and mental health using individual level panel data for private-sector employees in Germany. We first estimate the effect of firm-level workforce reductions on mental health, finding a strong, negative, and statistically significant relationship. We then extensively examine the role of subjective job insecurity as mediating variable and its importance relative to other possible channels for the effect of workforce reduction on mental health. Eventually, as an extension to our analysis, we use life satisfaction as alternative outcome variable.